Meta-Analysis: Effectiveness of artificial feeding to increase growth rate and reproduction quality of Monopterus albus species - Santosa, Tomi Apra; Putri, Rani Dwi Suci Hd; Sumarmin, Ramadhan; Putri, Dwi Hilda; Razak, Abdul (Jurnal Biologi Udayana, 2021)
The use of artificial feed for fish farming has been widely used at this time, however, it is not yet known the significant effect of artificial feed on the growth and reproduction rate of Monopterus albus . This study aims to determine the effectiveness of artificial feeding on the growth and reproduction rate of Monopterus albus species. This research is meta-analysis research. The data source comes from a search of 18 national and international articles published in 2010-2020 related to feeding the Monopterus albus species. Data obtained from google scholar database, DOAJ, ScienceDirect, sagejournal, Springer, and IEEE. The data analysis technique is a qualitative descriptive analysis with JASP software. The results showed that 35% of artificial feeding affected the growth of Monopterus albus and 28.5% affected the reproductive rate with an effect size of 1.2. This shows that artificial feeding has an effect of 0.334 in increasing the growth and reproductive quality of Monopterus albus .